The Effect of Fermentation on The Physicochemical Properties and Antioxidant Activity of Arrowroot (Maranta Arundinacea L.) Flour - Alifa Rahma Faradiani; Nabila Faradina Iskandar; Muhammad Iqbal Fanani Gunawan; Winangsit Sekar Mawarti; Geralddio El Nissi (Universitas Bumigora, 2026)
Arrowroot (Maranta arundinacea L.) is a gluten-free local starch source with high nutritional and bioactive compound potential, which is often found processed into flour. Modification through fermentation, either spontaneous or starter-assisted, may enhance its physicochemical properties and antioxidant activity. This study aimed to observe the effect of the fermentation process on arrowroot flour. The process included peeling, soaking, fermentation, drying, and milling, followed by proximate, color, acidity, phenolic content, and antioxidant assays (DPPH, IC50). The experiments employed a Completely Randomized Design (CRD) with two replicates. Results showed that both spontaneous and starter-assisted fermentation decreased the moisture and ash content significantly, but did not significantly affect the fat and protein content of the modified arrowroot flour. However, both fermentation processes decreased the total phenol content of modified arrowroot flours and ultimately reduced their antioxidant capacities, leading to the high IC50 concentration of modified arrowroot flour. Regardless of that, fermentation significantly improved the appearance of arrowroot flour, with starter fermentation resulting in a lighter colored flour (L* = 96.87 ± 0.45) and a slight red and yellow hue (a* = 1.63 ± 0.02; b* = 9.97 ± 0.43). This study concluded that fermentation, both spontaneous and starter-assisted, improved the color of arrowroot flour but did not enhance its chemical properties and antioxidant capacity. These results could be utilized to determine a more effective method to increase the functional properties of arrowroot flour.